INNER CONFLICT OF CHARACTERS IN EDWARD ALBEE’S THREE TALL WOMEN: AN OVERVIEW OF WOMEN’S LIFE IN MODERN LITERATURE - Nur Fadillah (JOEL: Journal of Educational and Language Research, 2021)
This study aims to analyze the inner conflict faced by the three women of the play where the characters feel regret with their past life and also tries to reveal the women’s life that describe the characteristics of modern literature. The study focuses on intrinsic elements of the play, especially the characters’ conversation. To explain the regret of the characters, the writer uses psychoanalysis of Sigmund Freud and analyzes the symptoms of regret and despair. This analysis also relates the play of Three Tall Women with the characteristics of modernist literary that presented the condition of society and women’s life. The primary data is taken from the script of Edward Albee’s Three Tall Women itself. After the analysis is done, the writer found that each woman in Three Tall Woman faces the inner conflict that makes them questioning what was they did wrong. The three of them feels regret to what happen with their life in the past and wish that the other women not to face it in their future life. In addition, the characteristics of modern literature is reflects the condition of the society where the story was written. The play Three Tall Women reflects the condition of people at the time until nowadays because people have done many things but still regret and wish to come back to their life in the past before the death come to them